Enhancing the Performance of the Air Force Central Hospital Staff by Organizational Citizenship Behavior and Knowledge Sharing - Hermawan, Ari; Sanusi, Anwar; Supriadi, Bambang (Indonesian Journal of Advanced Research, 2024)
This research aims to analyze the influence of organizational citizenship behavior (OCB) on performance through knowledge sharing at RSPAU Indonesia. This research was conducted in RSPAU Indonesia, located in the Adi Sutjipto Air Base office complex in Yogyakarta. The population of this research is all operational members of medical, nursing and other health personnel of RSPAU in Indonesia who are based on experience. At the same time, they are on duty, so they can assess OCB and measure knowledge sharing and performance. The sampling technique used was proportional random sampling, so the sample size was 167 samples of RSPAU Indonesia members from a population of 923. The data collection procedure in this research is to use a questionnaire, which will be analyzed using descriptive analysis. The research results show that voluntary Behavior is performed by members of an organization outside of specific tasks but contributes to the organization's overall effectiveness. Meanwhile, knowledge sharing is a process where individuals or groups share knowledge, experience and information with other people. The performance results are obtained by organizations or individuals when achieving organizational goals. Knowledge sharing as an intervening variable also mediates the performance of the OCB on staff. OCB has a significant influence on staff performance if met diated by knowledge sharing. I hope this research explains the success of RSPAU Indonesia in anticipating the dynamics of rapid changes in the world of health after the COVID-19 pandemic with its various complexities and problems. This research contributes to hospital leaders improving staff performance by looking at the influence of OCB on improving performance, both directly and indirectly, through knowledge sharing.